Analisis Technology Acceptance Model (TAM) Terhadap Pengguna Aplikasi Mobile Banking - Agus Siswoyo; Bambang Setyobudi Irianto (Politeknik Ganesha Medan, 2023)
Mobile banking application users have increased rapidly, but in its use there are still many problems experienced by users. This study aims to determine the level of user acceptance of the mobile banking application of a national bank using the Technology Acceptance Model (TAM) approach. In this study using the TAM framework, namely perceived usefulness, perceived ease of use, attitude to use, behavioral intention, and use of the actual system. The research was conducted on mobile banking application users in Tegal City using a purposive convenience sampling technique, obtained 104 respondents. The type of data used is primary data, namely data obtained directly from respondents. Methods of data collection using a questionnaire. The data analysis method uses the Partial Least Square (PLS) statistical test approach. The results showed that perceived ease of use had an effect on perceived benefits, perceived ease of use had an effect on attitudes of use, perceived benefits had no effect on attitudes of use, attitudes of use had had an effect on behavioral intentions, and behavioral intentions had had an effect on system use. The implications of the results of this study are input for banks to continue to improve mobile banking services in order to increase the number of mobile banking application users.